Cat Scratch Disease: A Diagnostic Challenge in Cervical Lymphadenopathy - Bipin Kishore Prasad; Yamuna Ranganathan; Gunjan Dwivedi; Devika Gupta (Bengal Journal of Otolaryngology and Head Neck Surgery, 2024)
Introduction: Cat scratch disease typically manifests as long standing regional lymphadenopathy, though clinical features may cover a wide spectrum. Lack of definite history of cat scratch, atypical presentation, non-availability of serological tests and misleading needle cytology may often lead to delay in diagnosis.